Association between plasma dipeptidyl peptidase-4 activity to brain-derived neurotrophic factor ratio and depressive symptoms in middle-aged and older adults with normal glucose tolerance: A cross-sectional study. (13th September 2020) - Zheng, Tianpeng; Chen, Xu; Ge, Bo; Chen, Bo; Qin, Linyuan; Tian, Li; Gao, Yun; Hu, Xueping; Xiao, Liuping; Pan, Haidong; Chen, Yujie
Abstract: Objectives: Attenuation of brain-derived neurotrophic factor (BDNF) availability and increased dipeptidyl peptidase-4 (DPP4) activity have both been reported to link to the pathogenesis of depression. The aim of this study was to test the correlation between depressive symptoms and plasma DPP4 activity to BDNF ratio (DBR). Methods: We evaluated DPP4 activity, BDNF, oxidative stress parameters and inflammatory markers and calculated DBR in a cross-sectional sample of 1640 non-diabetic participants. Results: DPP4 activity was negatively related to BDNF in participants with and without depressive symptoms ( r = −0.351 and r = −0.404, p <.001). Nitrotyrosine and 8-iso-PGF2a mediated 18.4 and 12.6% of the total effect of DPP4 activity on BDNF, respectively. 8-iso-PGF2a, nitrotyrosine, C-reactive protein, interleukin-6 and PHQ-9 score progressively increased across DBR quartiles. Participants whose DBRs were in the highest quartile had 2.64-fold increased odds (OR = 3.03) of depressive symptoms. The depressive symptoms risk increased more with lower levels of BDNF and higher levels of DPP4 activity ( p <.05). Conclusions: Our data suggested inverse correlation between DPP4 activity and BDNF through the oxidative stress mediator. The positive relationship between DBR and depressive symptoms risk raises feasibility of identifying DBR as a novel biological marker or even a possible therapeutic target for depression.